Abdurauf Fitrat's module on the use of pedagogical training - Sh.A. Abdujalilova (Zien Journals, 2022)
The article analyzes the issue of Abdurauf Fitrat's module on the use of pedagogical education.
Keywords: Fitrat; training; pedagogy; module